Laboratory validation of a resource quality-based conceptual framework for organic matter management - Vanlauwe, Bernard; Gachengo, CN; Shepherd, Keith D.; Barrios, E.; Cadisch, Georg; Palm, Cheryl A. (Wiley, 2005)
Organic resources (ORs) are essential inputs in tropical farming systems and their decomposition dynamics are related to their quality. A Decision Support System (DSS) for organic N management has been proposed earlier that subdivides ORs in four classes depending on their N, lignin, and soluble polyphenol contents. To validate this DSS, a 28-d aerobic incubation experiment was initiated with 32 ORs, mostly crop and tree residues, applied to a sandy loam soil. The ORs contained 1.4 to 53.2 g kg?1 of N, 25 to 295 g kg?1 of lignin, and 4 to 148 g kg?1 of soluble polyphenols. In vitro dry matter digestibility (IVDMD) ranged from 70 to 820 g kg?1 After 28 d, CO2–C production varied between 199 and 905 mg CO2–C kg?1 soil, and mineral N contents ranged from 5 to 109 mg N kg?1 soil. Based on N mineralization data, three classes of ORs were evident: Class A with N release > 0, Class B with N release approximately 0, and Class C with N release < 0 (N immobilization). Criteria to separate those classes were based on the OR N and polyphenol content and cut-off values between the classes agreed well with those proposed in the original DSS. For Class A ORs, N mineralization was negatively related to their lignin/N ratio (except for Gliricida residues) and for Class C ORs, N immobilization was positively related to their N content. Short-term mineralization data supported the existence of three classes of ORs instead of four originally proposed by the DSS. However, ORs also govern other functions, operating in the medium to long term, and for these functions, the original four-class concept may be proven valid.